Flight Seasonality of Dragonflies (Insecta, Odonata) in Northeastern Ukraine - Khrokalo, L.A.; Sheshurak, P.M. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Data on seasonal flight periods of Odonata in Northeastern Ukraine (Kyiv, Chernigiv, Sumy, Chekasy and Kharkiv administrative regions) based on field observations and a review of material collected during 1992–2004 are provided. It resulted in revised datasets on flight seaso- nalities for Chalcolestes parvidens Artobolevsky, Coenagrion armatum Charpentier, Brachytron pratensis Mueller, Aeshna affinis van der Linden, Anax imperator Leach, Gomphus vulgatissimus Linnaeus, Ophiogomphus cecilia Geoffroy, Cordulia aenea Linnaeus, Epitheca bimaculata Charpentier, Sympetrum danae Sulzer, Leucorrhinia rubicunda Linnaeus and L. caudalis Charpentier. The graphs of flight seasonalities of 13 frequently occurred species are plotted. All 55 species recorded are distributed among six seasonally defined groups. Own field data on the numbers of species occurring during seasons of year as adults, and the data from the literature are compared.